Experiencing Design “Pleasures”: Framework for Pleasurable Experiences On Designed Objects - Achmad Syarief (ITB Journal Publisher, LPPM ITB, 2008)
This paper explores the importance of human perceptual experiences toward objects, an effort to understand how human (as users of object) experiencing pleasures when interacting with a designed object. Having the purpose to explore the theoretical structure of human and object interaction, the paper contextualizes the concept of pleasurable experience in product use by (1) understanding the conceptual traces of “pleasure in design” in the history of design thinking (e.g. modernism and post-modernism), (2) correlating the identified traces with research results from other related field (e.g. cognitive psychology) to clarify the conceptual mechanism of human pleasurable experience, and (3) synthesizing results to define the theoretical framework in assessing pleasurable experience when human interact with a designed object. Following the path of Patrick Jordan’s theory on the pleasure in human factors, the study indicates that there are four identified functions of pleasure in product use: pleasure of using, pleasure of interacting, pleasure of understanding, and pleasure of owning. Those dimensions represent the experiential aspect of arousal (on the continuum of temporal – perpetual) and interactivity (on the continuum of individual – group).